Analisis Tingkat Kesehatan Bank Dengan Metode CAMEL Pada Laporan Keuangan PT. BPRS LT - Nur Safira Aulia Nurul Mahmudah; Abdurrahman Faris Indriya Himawan; Anita Akhirruddin (ILTIZAM Journal of Shariah Economics Research, 2022)
Existence in banking as a fund-raising institution in the community has increased, marked by an increase in the distribution of public funds towards the banking sector. This increase also increases the risks faced by banks. Based on this, it is important for banks to implement prudential banking to maintain their health. Measuring the soundness level of a bank has been regulated based on Bank Indonesia regulations by issuing SK No. 30/11/KEP/DIR April 30, 1997 concerning procedures for assessing the soundness of a bank which contains aspects of research objectives are banking. Financial performance can be reviewed and assessed using the CAMEL approach, which is a method that includes Capital, Asset Quality Assets, Management, Equity, Liquidity. This research was conducted with the aim of assessing financial performance. While the method used in this research is descriptive qualitative.Keywords: bank, bank health, financial statements, CAMEL